2013
DOI: 10.1159/000345989
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal Is Better than Oral: Observational Research of the Satisfaction of Caregivers of Patients with Alzheimer’s Disease Treated with Rivastigmine

Abstract: Background and Aims: Poor adherence to anti-dementia drugs is common among patients with Alzheimer’s disease. This study evaluated whether caregivers were more satisfied with, and patients more adherent to, transdermal rivastigmine than oral rivastigmine. Methods: Neurologists, psychiatrists and geriatricians collected sociodemographic and clinical data from 1,078 patients and administered the Treatment Satisfaction with Medicines (SATMED-Q) and the Morisky-Green questionnaires to their caregivers at outpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 72 publications
5
23
1
Order By: Relevance
“…This finding therefore suggests that transdermal application may increase treatment satisfaction among caregivers and help to overcome common practical barriers to adherence [4]. In contrast to the results of Boada and Arranz [8], however, our study found no evidence of an association between satisfaction with and adherence to patch treatment. This inconsistency in the findings may be attributed to the larger sample size used in the former study and the differential use of adherence and satisfaction measurements [i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding therefore suggests that transdermal application may increase treatment satisfaction among caregivers and help to overcome common practical barriers to adherence [4]. In contrast to the results of Boada and Arranz [8], however, our study found no evidence of an association between satisfaction with and adherence to patch treatment. This inconsistency in the findings may be attributed to the larger sample size used in the former study and the differential use of adherence and satisfaction measurements [i.e.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, the proportion of caregivers reporting ‘often' or ‘always' engaging in a non-adherent behaviour was less than 10% at both time points. These findings mirror the results of an earlier study of patients using transdermal rivastigmine, which identified similar levels of adherence (65%) [8]. However, as adherence was assessed by self-report, it is possible that the true level of adherence may have been lower than observed here.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A 9.5 mg/24 h (10 cm 2 ) patch was approved in 2007 by the FDA for mild-to-moderate AD, and a 13.3 mg/24 h (15 cm 2 ) patch was approved in 2013 for severe AD. The advantages of the patch compared with oral administration include increased adherence, improved tolerability, continuous drug delivery, and reduced fluctuations in drug concentration [27,28]. Use of the patch compared with the capsule may also allow a greater percentage of patients to reach and maintain the maximum doses of rivastigmine [29].…”
Section: Rivastigminementioning
confidence: 99%
“…[22][23][24] In practical terms, transdermal delivery has a number of advantages over oral capsules for patients with AD and their caregivers; the patch acts as a visual reminder that medication has been taken; 25 patch administration is easier, particularly in patients who are confused or display behavioral problems; 25 patch delivery is well-suited for patients who have difficulty swallowing. Although caregiver preference for transdermal versus oral formulations has not been confirmed in a sub-population of patients with severe AD, it is anticipated that the simple treatment regimen offered by a transdermal patch would also appeal to caregivers of patients with more advanced disease.…”
mentioning
confidence: 99%